Development For Tibetans, But By Whom? - Jue, Diana (Consilience, 2011)
The Tibet-China debate is entrenched in ethnic history, politics, and tension. Regardless of these realities, Tibetans throughout China’s underdeveloped West are among the poorest nationalities in the country. These field notes highlight and evaluate development efforts instated by three types of entities: the state, foreign development organizations, and local Tibetan development organizations. Many people want to help Tibet, but who is the most appropriate and able?